PENGARUH DIGITAL BANKING TERHADAP NILAI PERUSAHAAN PERBANKAN: Studi Pada PT. Bank Negara Indonesia (Persero) Tbk - Irwan Moridu (Jurnal Riset Akuntansi Politala, 2020)
The purpose of this study is to look at and analyze the effect of digital banking on the profits of banking companies by studying at PT. Bank Negara Indonesia (Persero) Tbk during 2013 - 2019. The method used is descriptive quantitative in which the data is processed using multiple linear regression. The data collection method is a non-participant observation by taking data from financial statements. The results of the study found that an increase in the number of financial transactions using Digital Banking, namely SMS Banking, Mobile Banking, and Internet Banking, partially did not affect the increase in profits, this is possible because of the inconvenience and doubt of customers in the use of Digital Banking, while simultaneously the results of this study The results show that the effect is not significant, meaning that overall Digital Banking is influential, although not significantly to PT. Bank Negara Indonesia (Persero) Tbk.